Pap smear in Early Detection of Cervical Precancerous Lesions in Erbil - Avin Wlya Muhammad; Haitham Issa Bahoo (Advanced Medical Journal)
Background and objectives: Cervical cancer remains common. This may be because Iraq has no cervical cancer screening or human papilloma virus vaccination program. The goal of the study is to figure out how well the Pap smear works as a way to find cervical precancerous lesions also identify the prevalence of cervical cancer among women and to identify the potential risk factors for cervical cancer.